1993
DOI: 10.1007/bf01658926
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative care of the elderly patient

Abstract: Surgical risk increases with age, primarily from loss of cardiac and pulmonary reserve. Complications are tolerated poorly by the elderly, emphasizing the importance of their prediction and prevention. Surgical risk in this population is significant, but with careful preoperative assessment and perioperative management acceptable morbidity and mortality are possible. This review proposes a general approach to the elderly surgical patient and applies it to the most significant sources of morbidity and mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
7

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(43 citation statements)
references
References 44 publications
0
36
0
7
Order By: Relevance
“…Brown reported approximately one-quarter of adults aged 65 and older experience delirium during hospitalization [3]. Ergina suggested that this may be because older adults have disproportionably more operations than younger adults, and also because the elderly population is growing [7]. All of the patients in our study were under general anesthesia, and one potential candidate mechanism of cognitive impairment is general anesthesia itself [6].…”
Section: Discussionmentioning
confidence: 91%
“…Brown reported approximately one-quarter of adults aged 65 and older experience delirium during hospitalization [3]. Ergina suggested that this may be because older adults have disproportionably more operations than younger adults, and also because the elderly population is growing [7]. All of the patients in our study were under general anesthesia, and one potential candidate mechanism of cognitive impairment is general anesthesia itself [6].…”
Section: Discussionmentioning
confidence: 91%
“…The safety of these treatments has increased due to improvements in preoperative evaluations, perioperative care, minimally invasive surgical procedures, and other advances in medical technology [3]. However, many elderly individuals suffer from major organ function deterioration as well as cardiovascular and respiratory comorbidity [4,5], and surgery and postoperative complications in such patients can therefore be fatal. The immediate postoperative fatality rate ranges from 5-20% [6].…”
Section: Discussionmentioning
confidence: 99%
“…Variability has also been observed across multiple patient-reported outcome domains (e.g., reduction in pain severity and improvement in quality of life) and other clinical outcomes (e.g., change in spinal flexion, improvement in muscle power, or change in neurological status). Previous work, which focused on identifying patient and surgical/ medical management factors that may contribute to this variation in outcomes, found there were several relevant biological factors (e.g., increased age [3][4][5][6], minority race/ ethnicity [7][8][9][10][11][12], and comorbid conditions [13][14][15]) and social factors (e.g., low socioeconomic status [16,17] and poor social support [18]). The presence of depressive symptoms has also been related to poor recovery.…”
Section: Introductionmentioning
confidence: 99%